a)
![((\frac{18}{2 \sqrt{6} } - \frac{24}{3 \sqrt{6} } - \frac{6}{ \sqrt{6} } ) - ( \frac{8}{5 \sqrt{6} } - \frac{24}{10 \sqrt{6} } ) - ( \frac{3}{ \sqrt{6} } - \frac{12}{3 \sqrt{6} } ) ((\frac{18}{2 \sqrt{6} } - \frac{24}{3 \sqrt{6} } - \frac{6}{ \sqrt{6} } ) - ( \frac{8}{5 \sqrt{6} } - \frac{24}{10 \sqrt{6} } ) - ( \frac{3}{ \sqrt{6} } - \frac{12}{3 \sqrt{6} } )](https://tex.z-dn.net/?f=%28%28%5Cfrac%7B18%7D%7B2+%5Csqrt%7B6%7D+%7D++-++%5Cfrac%7B24%7D%7B3+%5Csqrt%7B6%7D+%7D++-++%5Cfrac%7B6%7D%7B+%5Csqrt%7B6%7D+%7D+%29+-+%28+%5Cfrac%7B8%7D%7B5+%5Csqrt%7B6%7D+%7D++-++%5Cfrac%7B24%7D%7B10+%5Csqrt%7B6%7D+%7D++%29+-+%28+%5Cfrac%7B3%7D%7B+%5Csqrt%7B6%7D+%7D++-+++%5Cfrac%7B12%7D%7B3+%5Csqrt%7B6%7D+%7D+%29+)
b)
![( \frac{2}{3 \sqrt{2} } + \frac{5}{ \sqrt{8} } ) - ( \frac{3 \sqrt{2} }{2} - \frac{1}{3 \sqrt{2} } ) ( \frac{2}{3 \sqrt{2} } + \frac{5}{ \sqrt{8} } ) - ( \frac{3 \sqrt{2} }{2} - \frac{1}{3 \sqrt{2} } )](https://tex.z-dn.net/?f=%28+%5Cfrac%7B2%7D%7B3+%5Csqrt%7B2%7D+%7D++%2B++%5Cfrac%7B5%7D%7B+%5Csqrt%7B8%7D+%7D+%29+-+%28+%5Cfrac%7B3+%5Csqrt%7B2%7D+%7D%7B2%7D++-++%5Cfrac%7B1%7D%7B3+%5Csqrt%7B2%7D+%7D+%29)
c)
![( \frac{4}{5 \sqrt{2} } + \frac{3}{ \sqrt{8} } ) - ( \frac{5 \sqrt{2} }{4} - \frac{3}{ \sqrt{2} } ) ( \frac{4}{5 \sqrt{2} } + \frac{3}{ \sqrt{8} } ) - ( \frac{5 \sqrt{2} }{4} - \frac{3}{ \sqrt{2} } )](https://tex.z-dn.net/?f=%28+%5Cfrac%7B4%7D%7B5+%5Csqrt%7B2%7D+%7D++%2B++%5Cfrac%7B3%7D%7B+%5Csqrt%7B8%7D+%7D+%29+-+%28+%5Cfrac%7B5+%5Csqrt%7B2%7D+%7D%7B4%7D+-++%5Cfrac%7B3%7D%7B+%5Csqrt%7B2%7D+%7D++%29)
Multumesc!
Răspunsuri la întrebare
Răspuns de
2
Răspuns
Explicație pas cu pas:
Anexe:
![](https://ro-static.z-dn.net/files/dff/e7af851cd3233f3f603079c2589d27d9.jpg)
patrick7170:
multumesc
Răspuns de
2
a)
[9/(√6)-8/(√6)-6/(√6)]-[16/(10√6)-24/(10√6)]-[3/(√6)-4/(√6)]=
=(9-8-6)/√6-(16-24)/10√6-(3-4)/√6=
=(-5+1)/√6+8/10√6=
=-4/√6+8/10√6=
=(-40+8)/10√6=
=-32/10√6=
=-32√6/60=
=-8√6/15
b)
(2/3√2+5/2√2)-(3/2√2-1/3√2)=
=2/3√2+5/2√2-3/2√2+1/3√2=
=3/3√2+2/2√2=
=1/√2+1/√2=
=2/√2=
=2√2/2=
=√2
c)
(4/5√2+3/2√2)-(5/4√2-3/√2)=
=4/5√2+3/2√2-5/4√2+3/√2=
=(4+15)/5√2+(6-5)/4√2=
=19/5√2+1/4√2=
=(76+5)/20√2=
=81/20√2=
=81√2/40
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă